Timescales of inlet morphodynamic forced by tides and waves - Vu, Thi Thu Thuy (2020)
This paper analyses tidal records using a 24.5 hour moving window approach to find Tmorph and provides relationships between Tmorph and the external forcing from waves and tides for different coastal inlets in New South Wales, Australia. Response to extreme changes in forcing depends strongly on bay/inlet size; from small inlets which open and close several times every year to larger systems where the effect of even the most severe weather events is not- or is barely measurable via changes to the inlets hydraulic performance. Outcome can be used in coastal inlet management without extensive river flow and bathymetry data.